Regulation of ΔNp63α by NFκB - Sen, Tanusree (Landes Bioscience, 2010)
ΔNp63α, the dominant negative isoform of the p63 family is an essential survival factor in head and neck squamous cell carcinoma. This isoform has been shown to be downregulated in response to several DNA damaging agents, thereby enabling an effective cellular response to genotoxic agents. Here, we identify a key molecular mechanism underlying the regulation of ΔNp63α expression in response to extrinsic stimuli, such as chemotherapeutic agents. We show that ΔNp63α interacts with NFκB in presence of cisplatin. We find that NFκB promotes ubiquitin-mediated proteasomal degradation of ΔNp63α. Chemotherapy-induced stimulation of NFκB leads to degradation of ΔNp63α and augments trans-activation of p53 family-induced genes involved in the cellular response to DNA damage. Conversely, inhibition of NFκB with siRNA-mediated silencing NFκB expression attenuates chemotherapy induced degradation of ΔNp63α. These data demonstrate that NFκB plays an essential role in regulating ΔNp63α in response to extrinsic stimuli. Our findings suggest that the activation of NFκB may be a mechanism by which levels of ΔNp63α are reduced, thereby rendering the cells susceptible to cell death in the face of cellular stress or DNA damage.